A PROPOSED MODEL FOR PREDICTING THE FINANCIAL DISTRESS OF PRIVATE CONVENTIONAL BANKS IN SYRIA: AN EMPIRICAL STUDY - Salhani, Alaa (PEOPLE: International Journal of Social Sciences, 2019)
This study aims to find the best set of financial ratios that can be used to predict the financial distress of private conventional banks in Syria and to distinguish between distressed and non-distressed banks in the first and second year before the distress. In order to warn the concerned parties to intervene and take corrective actions in a timely manner and to restore the health of these banking institutions. To achieve this, a stepwise discriminant analysis was used and 21 financial ratios were calculated for a sample of 11 banks for a period between the years (2010-2016). The following proposed model was reached: Z = 14.746 (D/A) + 35.069 (L/A) -15.899 (NFE/A) -5.134 (NPM) -26.076. Test of the model has been done, and it was found to be able to predict the financial distress and distinguish between distressed and non-distressed banks with an accuracy rate 100% in the first and second year before the distress.